Synthesis and anticorrosion characterization of marine geopolymer concrete - Li, Xing (Universidad Michoacana de San Nicolas de Hidalgo, 2020)
Concrete exposed to seawater is easily corroded by seawater, for example, heat-cool and dry-wet cycle, SO2-4 and Mg2+ corrosion and Cl- penetration. Geopolymers are considered as a good application of concrete. In this work, different geopolymers were synthesized to evaluate their resistance to sea water corrosion. To applicate geopolymers in marine engineering, the silica sand and steel fiber (8.5 mm in length and 0.2 mm in diameter) were first prepared in geothermal clay to synthesize geopolymer concrete. After that, metakaolin based geopolymer and geothermal clay based geopolymer were cured in the sea water, dry-wet cycle, heat-cool cycle. Then alkaliactivated binders based on metakaolin, fly ash and slag without curing were exposed directly in air, Na2SO4 and MgSO4 solutions. In the end, reinforced alkali activated metakaolin-tailing concrete were exposed in sea water though electrochemical accelerated corrosion to observe the corrosion of steel bars by chloride ions. In a transitional experiment for synthesizing geopolymer concrete, about 10% to 60% silica sand replaced geothermal clay to synthesize mortars first and then a comparison was made with and without steel fiber. Their mechanical behavior and microstructures were studied. For studying the resistance to different seawater corrosion factors, different geopolymers were prepared and cured in different sea water corrosion conditions. Then the products were characterized by scanning electron microscopy (SEM), x-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR) to evaluated morphology and microstructures, and mechanical tester for compressive strength. Besides, 29Si nuclear magnetic resonance (NMR) spectra were used to study the microstructure of products, the short-range ordering and the molecular structure.

El concreto expuesto al agua de mar es fácilmente corroído por el agua de mar, por ejemplo, el ciclo de calor-frío y seco-húmedo, la corrosión de SO2- 4 y Mg2+ y la penetración de Cl-. Los geopolímeros se consideran una buena aplicación del hormigón. En este trabajo, se sintetizaron diferentes geopolímeros para evaluar su resistencia a la corrosión del agua de mar. Para aplicar geopolímeros en ingeniería marina, arena de sílice y fibra de acero (8.5 mm de longitud y 0.2 mm de diámetro) se prepararon primero en arcilla geotérmica para sintetizar hormigón geopolímero. Después, el geopolímero a base de metacaolín y geopolímero a base de arcilla geotérmica se curaron en agua de mar, ciclos de seco-húmedo y calor-frío. Luego, los aglutinados activados con álcali basados en metacaolín, cenizas volantes y escoria sin curar se expusieron directamente al aire, soluciones de Na2SO4 y MgSO4. Al final, el concreto reforzado metacaolín-jales activado con álcali el hormigón se expuso en agua de mar a través de la corrosión acelerada electroquímica para observar la corrosión de las barras de acero por los iones de cloruro. En un experimento de transición para sintetizar concreto activado con álcali, aproximadamente 10% a 60% de arena sílice reemplazó la arcilla geotérmica para sintetizar morteros primero y luego se realizó una comparación con y sin fibra de acero. Se estudiaron su comportamiento mecánico y microestructuras. Para estudiar la resistencia a diferentes factores de corrosión del agua de mar, se prepararon y curaron diferentes geopolímeros en diferentes condiciones de corrosión del agua de mar. Después, los concretos fueron caracterizados por microscopía electrónica de barrido (SEM), difracción de rayos X (XRD), espectroscopía infrarroja por transformada de Fourier (FTIR) para evaluar su morfología y microestructuras, y prueba mecánica de resistencia a la compresión.
Instituto de Investigaciones Metalúrgicas. Doctorado en Ciencias en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-D-2020-0793; Geopolímero; Microestructura; Espectros de RMN; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2657